Answer: 1) 25b 2) ac 3)ba
1) Since b is unknown, your answer will be 25b
2) Since both variables, a and c, are unknown, your answer will be ac
3) Since both are unknown here, it will be ba!
For this case, we have the following expression:
![-3x + x + 5](https://tex.z-dn.net/?f=-3x%20%2B%20x%20%2B%205)
We simplify the expression:
If we add similar terms, taking into account that different signs are subtracted and the sign of the greater one is placed, we have that ![-3x + x = -2x](https://tex.z-dn.net/?f=-3x%20%2B%20x%20%3D%20-2x)
So, we have to:
![-3x + x + 5 = -2x + 5](https://tex.z-dn.net/?f=-3x%20%2B%20x%20%2B%205%20%3D%20-2x%20%2B%205)
Answer:
-3x + x + 5 = -2x + 5
C The answer is y=1.560-22.105
For this case we have to:
x: Let the variable representing the unknown number
We algebraically rewrite the given expression:
Twice a number plus 10, is represented as:![2x + 10](https://tex.z-dn.net/?f=2x%20%2B%2010)
Three times that number less 4. is represented as:
![3x-4](https://tex.z-dn.net/?f=3x-4)
Thus, the complete expression is:
![2x + 10> 3x-4](https://tex.z-dn.net/?f=2x%20%2B%2010%3E%203x-4)
Subtracting 3x from both sides of the inequality:
![2x-3x + 10> -4\\-x + 10> -4](https://tex.z-dn.net/?f=2x-3x%20%2B%2010%3E%20-4%5C%5C-x%20%2B%2010%3E%20-4)
Subtracting 10 from both sides of the inequality:
![-x> -4-10](https://tex.z-dn.net/?f=-x%3E%20-4-10)
Equal signs are added and the same sign is placed:
![-x> -14](https://tex.z-dn.net/?f=-x%3E%20-14)
We multiply by -1 on both sides, taking into account that the sense of inequality changes:
![x](https://tex.z-dn.net/?f=x%20%3C14)
The solution is given by all values of "x" less than 14.
Answer:
![x](https://tex.z-dn.net/?f=x%20%3C14)